Flora Robotica - Mixed Societies of Symbiotic Robot-Plant Bio-Hybrids - Hamann, Heiko; Wahby, Mostafa; Schmickl, Thomas; Zahadat, Payam; Hofstadler, Daniel; Stoy, Kasper; Risi, Sebastian; Faina, Andres; Veenstra, Frank; Kernbach, Serge; Kuksin, Igor; Kernbach, Olga; et al. (Proceedings of the 2015 IEEE Symposium on Artificial Life (IEEE ALIFE'15))
Besides the life-as-it-could-be driver of artificial life research there is also the concept of extending natural life by creating hybrids or mixed societies that are built from natural and artificial components. In this paper we motivate and present the research program of the project flora robotica. Our objective is to develop and to investigate closely linked symbiotic relationships between robots and natural plants and to explore the potentials of a plant-robot society able to produce architectural artifacts and living spaces. These robot-plant bio-hybrids create synergies that allow for new functions of plants and robots. They also create novel design opportunities for an architecture that fuses the design and construction phase. The bio-hybrid is an example of mixed societies between 'hard' artificial and 'wet' natural life, which enables an interaction between natural and artificial ecologies. They form an embodied, self-organizing, and distributed cognitive system which is supposed to grow and develop over long periods of time resulting in the creation of meaningful architectural structures. A key idea is to assign equal roles to robots and plants in order to create a highly integrated, symbiotic system. Besides the gain of knowledge, this project has the objective to create a bio-hybrid system with a defined function and application -- growing architectural artifacts.